Eksplorasi Pengalaman Guru Dan Siswa Dalam Implementasi Tpack Berbantuan Live Worksheet: Sebuah Studi Fenomenologi di Kelas V SDN Kuncen Kota Madiun - Emi Kencanasari; Ibadullah Malawi; Nurhaji Nugraha (Tamilis Synex: Multidimensional Collaboration, 2025)
The integration of technology in learning is a necessity in the digital era, demanding teachers to have a comprehensive understanding known as TPACK (Technological Pedagogical Content Knowledge). Live Worksheet emerges as a digital tool that can mediate this integration. This study aims to explore the lived experience of teachers and fifth-grade students at SDN Kuncen, Madiun City, in implementing TPACK assisted by Live Worksheet in social studies learning. This research uses a phenomenological qualitative approach. Data were collected through in-depth interviews, participatory observation, and documentation of learning artifacts. Data analysis followed the steps of phenomenological reduction, imaginative variation, and synthesis of meanings. The findings reveal three main themes: (1) The teacher's experience in navigating the intersection of pedagogical, content, and technological knowledge when designing and implementing learning; (2) Students' experiences in constructing understanding through interactive and autonomous digital worksheets; and (3) The dynamics of pedagogical relationships that shift towards facilitation and collaborative exploration.